Loop I of U1 small nuclear RNA is the only essential RNA sequence for binding of specific U1 small nuclear ribonucleoprotein particle proteins. - Hamm, J (1988)
The binding of the U1 small nuclear ribonucleoprotein (snRNP)-specific proteins C, A, and 70K to U1 small nuclear RNA (snRNA) was analyzed. Assembly of U1 snRNAs from bean and soybean and a set of mutant Xenopus U1 snRNAs into U1 snRNPs in Xenopus egg extracts was studied. The ability to bind proteins was analyzed by immunoprecipitation with monospecific antibodies and by a protein-sequestering assay. The only sequence essential for binding of the U1-specific proteins was the conserved loop sequence in the 5' hairpin of U1. Further analysis suggested that protein C binds directly to the loop and that the assembly of proteins A and 70K into the RNP requires mainly protein-protein interactions. Protein C apparently recognizes a specific RNA sequence rather than a secondary structural element in the RNA.